Early Diagnosis of Abortion in Holstein Cows Using Homeostasis-electrolyte factors (calcium_potassium) - Nasrin Hajiabadi, Ezzatollah Fathi, Hossain Hamli (Drugs and Cell Therapies in Hematology, 2021)
Abortion in Holstein cows has been a very effective factor in profitability of active livestock units which has resulted in economic losses. There are various nutritional and infectious agents which play an important role in abortion occurrence. According to various studies, changes in mineral levels can be an efficient factor in early detection of some diseases in cows, such as abortion. In the present study, homeostasis-electrolyte factors including sodium, potassium, calcium and chlorine were investigated and measuring of some different hematological parameters, such as, complete blood test of aborted dairy cows, and the relationship between these factors and abortion in Holestein cows were examined. Forty pure-bred Holstein cows were selected from cattle ranches around Tabriz in East Azarbayejan-province. The blood samples of the two groups; control group cows (20 cows) and experimental group cows (20 cows) or the affected group were obtained, to identify hematological parameters and evaluate some homeostasis-electrolyte factors (Cl, Ca, K, Na). Based on the obtained results, calcium and potassium electrolyte indicators revealed a significant increase and decrease in sick or affected cows in comparison to the control group samples. According to the hematological indicators, no significant and meaningful difference was observed, although the level of these electrolytes in control group samples was higher than the experimental group samples. Evaluating and assessing the mentioned factors demonstrated that, the measurement of calcium and potassium electrolyte levels in blood plasma of the Holstein cows can be considered as an accurate and rapid indictor in early diagnosis and detection of aborted cases, moreover, it would be possible to examine and assess the health condition of these cows.